دار الترجمة في مطبعة نول كشور: خدماتها المعرفية والثقافية: The Translation Centre at the Nawal Kishore Press: Its Intellectual and Cultural Contributions - عبد الملك الرسول فوري (الدراسات الإسلامية, 2023)
This article introduces an Indian entrepreneur Nawal Kishore who was very enthusiastic about publishing Arabic and Islamic literature. It also sheds light on the services of the Nawal Kishore Press in translating Arabic literature into Persian and Urdu. Moreover, it surveys several books, which were translated by the translation centre of this press and assesses the quality of these translations. The paper also discusses the history of the translated works published by this translation centre. Sometimes the translated work proves the level of the translator’s abilities. Some other times the name of the translator is considered sufficient to guess the quality of the translation. The article also includes short biographical notes on the translators who played an important role in the development of this translation centre.